A Survey on Virtual Machine Scheduling Algorithms in Cloud Computing - Kumar, M; Suman; Singh, S (International Journal of Computer Sciences and Engineering, 2025)
In present scenario cloud computing is not a new term for scientist, engineers and researchers. It is used by people from varied walks of life ranging from organizations to mobile users. This technology allows many organization and individual users to take services, hardware, storage spaces and software on rent rather than setting up new infrastructure. With advancement in technology, cloud computing faces several challenges like power consumption, reliability, performance, bandwidth cost, security and privacy which needs to be addressed by researchers. This paper presents an overview of cloud computing technology and comparative analysis of virtual machine (VM) scheduling algorithms. VM scheduling algorithms are compared on basis on several parameters such as reliability, scalability, QoS, and environment. The comparison is further fine-tuned with quantified data.